2014
DOI: 10.1242/dev.114488
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific genome editing in Ciona embryos by CRISPR/Cas9

Abstract: The CRISPR/Cas9 system has ushered in a new era of targeted genetic manipulations. Here, we report the use of CRISPR/Cas9 to induce double-stranded breaks in the genome of the sea squirt Ciona intestinalis. We use electroporation to deliver CRISPR/Cas9 components for tissue-specific disruption of the Ebf (Collier/Olf/ EBF) gene in hundreds of synchronized Ciona embryos. Phenotyping of transfected embryos in the 'F0' generation revealed that endogenous Ebf function is required for specification of Isletexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
192
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(193 citation statements)
references
References 49 publications
1
192
0
Order By: Relevance
“…We therefore also performed analysis of the same crispants using Sanger sequencing of a limited number of individual clones from PCR products, as routinely reported to assess mutagenesis efficiency (Auer et al, 2014a;Jao et al, 2013;Stolfi et al, 2014;Varshney et al, 2015). For analyzed targets with good sequence coverage (n=12 or more), our analysis revealed that limited Sanger sequencing data strongly correlate with our MiSeq data: for all analyzed loci, Sanger sequencing of subcloned PCR fragments (1) reliably established a mutagenesis efficiency estimate ( Fig.…”
Section: Crispants Replicate Loss-of-function Phenotypesmentioning
confidence: 57%
See 2 more Smart Citations
“…We therefore also performed analysis of the same crispants using Sanger sequencing of a limited number of individual clones from PCR products, as routinely reported to assess mutagenesis efficiency (Auer et al, 2014a;Jao et al, 2013;Stolfi et al, 2014;Varshney et al, 2015). For analyzed targets with good sequence coverage (n=12 or more), our analysis revealed that limited Sanger sequencing data strongly correlate with our MiSeq data: for all analyzed loci, Sanger sequencing of subcloned PCR fragments (1) reliably established a mutagenesis efficiency estimate ( Fig.…”
Section: Crispants Replicate Loss-of-function Phenotypesmentioning
confidence: 57%
“…S5). This observation reveals that randomly generated in-frame alleles, which potentially maintain open reading frame integrity (yet nonetheless might impact amino acid residues important for protein function), are a major uncontrolled variable in the use of crispants induced by any method to directly assess loss-of-function phenotypes, both on a whole-embryo (Shah et al, 2015; this study) and on a tissue-specific (Ablain et al, 2015;Stolfi et al, 2014) scale.…”
Section: Crispants Replicate Loss-of-function Phenotypesmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, electroporation was successfully adapted to achieve tissue-targeted gene manipulation with plasmids that express gene editing tools like the CRISPR/Cas9 components under the control of tissue specific drivers 21,22 . Such approaches will quickly advance our understanding of the dynamics of GRNs and the potentially conserved signaling mechanisms, including transcription factor codes involved in tissue formation and the stepwise exit from pluripotency.…”
Section: Versatility and Potential Of Electroporation For Genetic Engmentioning
confidence: 99%
“…The Cripsr-Cas9 system was used in a study using the ascidian Ciona intestinalis (Stolfi et al 2014). This study, from Lionel Christiaen's group, reported the success of tissue-specific genome editing in this species.…”
Section: Introductionmentioning
confidence: 99%